The Effect of Consumer Analysis, Product Adaptation and Customer Equity on Purchase Decisions Consumers at PT Rim Syam Gold Bangkinang - Muhammad Rifal Sabri; Abshor Marantika (Dinasti International Journal of Education Management and Social Science, 2025)
The decision to purchase gold is a series of processes that consumers go through in determining their choice to buy gold, whether in the form of jewellery, precious metals, or derivative products. This study is designed to investigate the influence of the three variables, considered collectively and separately, within the framework of consumer buying decisions. Research data were obtained from primary and secondary sources through questionnaires, interviews, and documentation. In this study, data were obtained from a combination of primary and secondary sources, utilising several techniques, including the administration of structured questionnaires, in-depth interviews, and the review of relevant documentation. The population comprised all customers of PT RIM Syam Gold Bangkinang, while a total of 100 respondents were selected as the sample through an accidental random sampling method, whereby respondents were chosen based on their presence and readiness to respond during the survey period. The collected data were subsequently analysed using multiple linear regression to determine the extent to which the independent variables jointly and separately affect purchasing decisions. To test the proposed hypotheses, the study applied both the F-test to evaluate the overall explanatory power of the regression model and the t-test to assess the statistical significance of each coefficient, with all tests performed at a conventional 5% level of significance. This methodological design ensures that the empirical findings are supported by rigorous quantitative analysis. Findings demonstrate a significant positive impact of consumer analysis, product adaptation, and customer equity on gold-buying decisions, whether assessed together or separately. Among the three variables, consumer analysis is proven to be the most dominant factor influencing consumer purchasing decisions. This finding implies that companies should strengthen their understanding of consumer behaviour, optimize innovation strategies in product adaptation, and increase customer equity to maintain and improve consumer purchasing decisions.